2007
DOI: 10.1097/qad.0b013e328012b84d
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous meningitis in HIV-infected patients: drug susceptibility and clinical outcome

Abstract: The objective of this study was to identify prognostic factors of death in patients with tuberculous meningitis (TM) and show the impact of infection by multidrug-resistant strains on the outcome of this disease. We retrospectively analysed clinical charts of HIV-infected patients with culture-confirmed TM attending our institution during 1996-2004. The following variables were associated with death during hospitalization: neurological signs at admission, a CD4 T-cell count less than 50 cells/microl and infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 8 publications
3
29
3
2
Order By: Relevance
“…Ten isolates had isolated resistance to single antituberculosis drugs. Because of multidrug-resistant strains, tuberculous meningitis was more frequent in patients who received irregular antituberculosis treatment [59,60]. Patients with multidrug-resistant tuberculous meningitis and HIV-infection have lower cure rates and higher mortality rates than patients with drug-susceptible tuberculous meningitis, and most patients die within 3 months [26,61].…”
Section: Drug-resistant Tuberculous Meningitis In Hiv-positive Patientsmentioning
confidence: 99%
“…Ten isolates had isolated resistance to single antituberculosis drugs. Because of multidrug-resistant strains, tuberculous meningitis was more frequent in patients who received irregular antituberculosis treatment [59,60]. Patients with multidrug-resistant tuberculous meningitis and HIV-infection have lower cure rates and higher mortality rates than patients with drug-susceptible tuberculous meningitis, and most patients die within 3 months [26,61].…”
Section: Drug-resistant Tuberculous Meningitis In Hiv-positive Patientsmentioning
confidence: 99%
“…In HIV infected patients, a lower CD4 cell counts [3,23], focal signs and altered consciousness on admission, were found to be a factor associated with poor prognosis [47]. Previous study found also an association between immune suppression, neurological deterioration at admission and poor prognosis in HIV infected TBM patients [6,48,49]. Some studies reported other factors associated with death including disease duration of more than 14 days, drug resistance TB and low serum sodium concentration [23,49].…”
Section: Issn: 2373-8995mentioning
confidence: 97%
“…The convergence of drug-resistant TB and HIV poses unique clinical challenges [1][2][3] ; among these, involvement of the central nervous system (CNS) presents one of the most difficult manifestations, with significant morbidity and mortality. [4][5][6][7] The emergence of HIV and drug-resistant TB as relentless forces in the TB epidemic has accelerated the push for innovative TB diagnostics. [8][9][10][11] The ideal method must diagnose TB from smear-negative specimens, identify resistance to at least INH and RIF, and perform under basic laboratory conditions at minimal cost.…”
Section: Discussionmentioning
confidence: 99%